SPECIALIZED NURSING TERMINOLOGY FOR PEOPLE WITH VISCERAL LEISHMANIASIS - Araújo, Diego Dias de; Bernardes, Tatielle Aparecida Almeida; Camisasca, Luiza Rodrigues; Lopes, Ana Beatriz Martins; Corrêa, Hérica Pinheiro; Silva, Daniel Vinícius Alves; Nascimento, Maria Naiane Rolim (Cogitare Enfermagem, 2023)
Objective: to create specialized Nursing terminology for the care of people with Visceral Leishmaniasis. Method: a methodological study carried out in two stages: identification of the relevant concepts in medical records of patients with chosen health priority admitted between 2017 and 2019 to a public and teaching hospital in the north of Minas Gerais, BR; cross-mapping of the concepts identified with the ICNP®. Results: a total of 57,797 simple and compound (with repetitions) concepts, were extracted, of which 624 were useful single concepts for the Nursing care to be provided to people with Visceral Leishmaniasis. 281 (45%) primitive concepts were identified as included in ICNP® 2019-2020, as well as 343 (55%) not included in the classification. The concepts related to Focus and Location stood out in the axes. Conclusions: a specialized ICNP® terminology was created for the care of people with Visceral Leishmaniasis, with potential impacts on the standardization of actions and on generation of indicators sensitive to the Nursing practice.